"Pretty Disgusted Honestly": Exploring Fans' Affective Responses on Facebook to the Modified Rules of Australian Football League Women's. (February 2022) - Pavlidis, Adele; Toffoletti, Kim; Sanders, Kellie
In this article, we argue that the "turn to affect" can provide a generative framework for working through key sticking points for women in sport. Through an analysis of the rule changes and subsequent social media comments in the lead-up to the inaugural Australian Football League Women's (AFLW) competition, we demonstrate the power of emotions for intensifying and resisting discussion about women's participation in male-dominated sport, as they accumulate through fan encounters on social media. Through a focus on the expression of emotions such as disappointment and contempt, we interrogate the collective workings of digital affects for constituting gendered knowledge production and subjectivity in sport contexts. We conclude with a discussion of the implications of feminist thinking for sport research and practice.